China's path to geopolitics: Case study on China's Iran policy at the intersection of regional interests and global power rivalry - Angela Stanzel (Stiftung Wissenschaft und Politik (SWP), 2022)
Chinese foreign policy is at the crossroads of regional interests and global power rivalry in the Middle East, especially in Iran. China's interests in the Middle East increasingly collide with those of the US, which has brought about a significant re-orientation of Chinese foreign policy on this region. Beijing is increasingly concerned with balancing US influence in the region. Relations with Iran offer China various possibilities for balancing US influence. A decisive factor for China's Iran policy are its regulatory ideas aiming to establish equality of influence between the major global powers in a given region, in this case the Middle East. Chinese discourse underpins the shifts in Chinese foreign policy in which hard or soft balancing is increasingly becoming a feature of a "geo-politicised" regional policy. This geostrategic regional policy with regard to Iran shows that China is gaining influence there at the expense of the United States. German and European actors need a deeper understanding of China's balancing policy. This would enable Germany and the EU to correctly assess and also question the rhetoric of the Chinese leadership. On this basis, Germany and the EU should adjust their engagement in Iran, especially with regard to the Iranian nuclear weapons issue. Moreover, the new German government should ensure that foreign policy actions in third countries are comprehensive and coordinated with the EU so as to meet the challenges posed by China. Such coordination must also be pursued within the transatlantic framework.
Keywords: 320